Effect of using crosswords on operating room students' learning in a Haematology course: A quasi experimental study - Mohsen Masoumian hosseini; Fateme Ruhabadi; Azam Gazarani; Akram Gazarani; Mona Larki (Zanjan University of Medical Sciences and Health Services, 2023)
Background and Objective: Learning can be promoted through learning games since they are fun and amusing with a competitive nature that creates a stimulating atmosphere in the classroom. The educational system puts an emphasis on student ownership and creative thinking as critical factors in learning. The present study aimed to investigate the effects of crossword puzzles on the learning of operating room students in a hematology course. Materials & Methods: The study was conducted based on a quasi-experimental pretest and post-test design with an intervention group (designing crossword puzzles) and a control group (solving crossword puzzles) at North Khorasan University of Medical Sciences in 2018. The participants were selected via the census sampling method. A total of 56 students were randomly assigned to control and intervention groups. They were divided into seven groups of four. The intervention was administered during the first 15-20 min of the seven sessions. The data collection instrument consisted of a questionnaire divided into two sections: assessing satisfaction and determining procedural knowledge. PRISM Statistics (version 7) was used for statistical analysis. A p-value of less than 0.05 was considered statistically significant. Results: The result of the independent t-test demonstrated that the crossword puzzle design group, compared to solving crossword puzzles, significantly improved the knowledge of hematology (P=0.0047). Paired t-tests illustrated that both groups had significant learning gains in the topics covered in the sessions (P<0.0001). Conclusion: The crossword puzzle design in this study proved to be an effective method to engage students, resulting in higher participation. In this study, crossword puzzles proved to be an effective teaching tool for learning hematology concepts.